Case Report: Biologic-free clinical remission following anifrolumab discontinuation in systemic lupus erythematosus—two-case reports - Hashimoto, Takako; Yasuoka, Hidekata (Frontiers in Lupus, 2026)
BackgroundAnifrolumab, a monoclonal antibody against the type I interferon receptor, has shown efficacy in systemic lupus erythematosus (SLE). However, sustained remission after drug discontinuation has been rarely reported.Case presentationWe reported two females with SLE who achieved biologic-free clinical remission after discontinuation of anifrolumab, with no major adverse events observed during or after treatment. Case 1: A 25-year-old woman with newly diagnosed SLE presented with active disease (SLEDAI-2K 14), including arthritis, facial rash, alopecia, mucosal ulcers, hypocomplementemia, and anti–double-stranded DNA antibody positivity. She was initially treated with prednisolone (PSL) and hydroxychloroquine (HCQ); however, a flare occurred during glucocorticoid (GC) tapering, and anifrolumab was initiated with concomitant methotrexate (MTX). The patient achieved clinical remission according to the Definition of Remission In SLE (DORIS) criteria, despite persistent hypocomplementemia and anti–dsDNA antibody positivity. After sustained remission, PSL was discontinued, MTX was tapered, and anifrolumab was discontinued after 25 months due to sustained clinical remission according to the DORIS criteria and patient preference related to work-related difficulty with long-term regular follow-up. She has remained in clinical remission for 6 months on HCQ and low-dose MTX. Case 2: A 22-year-old woman with SLE diagnosed at age 16 presented after disease relapse following GC withdrawal at age 21. At relapse, her disease activity was moderate (SLEDAI-2K 11), characterized by facial rash, alopecia, mucosal ulcers, leukopenia, hypocomplementemia, and anti–dsDNA positivity. She was treated with anifrolumab in combination with HCQ. Her disease activity achieved and maintained clinical remission according to the DORIS criteria, despite persistent hypocomplementemia and anti–dsDNA antibody positivity. Dose spacing and subsequent discontinuation of anifrolumab were attempted because of patient preference related to work-related limitations to long-term follow-up, and future pregnancy plans, and sustained remission was maintained. Even after switching to tacrolimus (Tac), she has maintained remission without anifrolumab for 12 months.ConclusionThese cases suggested that clinical remission could be maintained after discontinuation of anifrolumab in selected patients with SLE.